2010
DOI: 10.1890/09-1534.1
|View full text |Cite
|
Sign up to set email alerts
|

Ants mediate the structure of phytotelm communities in an ant‐garden bromeliad

Abstract: Abstract. The main theories explaining the biological diversity of rain forests often confer a limited understanding of the contribution of interspecific interactions to the observed patterns. We show how two-species mutualisms can affect much larger segments of the invertebrate community in tropical rain forests. Aechmea mertensii (Bromeliaceae) is both a phytotelm (plant-held water) and an ant-garden epiphyte. We studied the influence of its associated ant species (Pachycondyla goeldii and Camponotus femorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
(33 reference statements)
2
36
0
Order By: Relevance
“…We homogenized the water within leaf wells by sucking in and out with a pipet, before sucking out the content. Although less efficient than plant dissection, we and other researchers have already successfully used this technique [24], [27]. It was consistently used for all of the samples and most of the water (>95%) was collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We homogenized the water within leaf wells by sucking in and out with a pipet, before sucking out the content. Although less efficient than plant dissection, we and other researchers have already successfully used this technique [24], [27]. It was consistently used for all of the samples and most of the water (>95%) was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Invertebrates were sorted in the laboratory and preserved in 70% ethanol. They were identified to genus, species or morphospecies and enumerated (species lists in [21], [24]). Species abundance data (individuals per plant) were used to calculate evenness (Simpson index) and entropy (Shannon-Weaver index) for each invertebrate community.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ant species with different habitat preferences in terms of sun exposure determine the location of their associated epiphytes by installing their nests in certain parts rather than others of the tree crowns. In so doing, these ants indirectly drive the main environmental constraints on the aquatic habitat, thus mediating the structure and functioning of the aquatic community [8][9][10]. These plants can benefit from myrmecotrophy, protection from herbivores, and, in some cases, pollination [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the influence of two‐species mutualisms on communities was poorly explored (Savage & Peterson 2007), preliminary observations made on a single location suggested that mutualistic ants can influence the shape and size of their associated plants by determining the distribution of the seedling along gradients of incident light (Leroy et al. 2009), thereby affecting the taxonomic composition of invertebrate communities that depend on the same plant (Céréghino et al. 2010).…”
Section: Introductionmentioning
confidence: 99%